2020
DOI: 10.3847/1538-4357/ab6168
|View full text |Cite
|
Sign up to set email alerts
|

Do the TRAPPIST-1 Planets Have Hydrogen-rich Atmospheres?

Abstract: Recently, transmission spectroscopy in the atmospheres of the TRAPPIST-1 planets revealed flat and featureless absorption spectra, which rule out cloud-free, hydrogen-dominated atmospheres. Earthsized planets orbiting TRAPPIST-1 likely have either a clear or a cloudy/hazy, hydrogen-poor atmosphere. In this paper, we investigate whether a proposed formation scenario is consistent with expected atmospheric compositions of the TRAPPIST-1 planets. We examine the amount of a hydrogen-rich gas that TRAPPIST-1-like p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 81 publications
2
26
0
Order By: Relevance
“…This argument, plus the HST/WFC3-IR transit measurements, are strong arguments against the presence of H 2 -dominated envelopes around TRAPPIST-1 planets. This is also supported by recent calculations (Hori and Ogihara 2020 ) showing the total mass loss of hydrogen-rich envelopes around TRAPPIST-1 planets is anyway likely higher than the amount of hydrogen-rich gas they can accrete during their formation.…”
Section: Constraints From Numerical Modellingsupporting
confidence: 81%
See 1 more Smart Citation
“…This argument, plus the HST/WFC3-IR transit measurements, are strong arguments against the presence of H 2 -dominated envelopes around TRAPPIST-1 planets. This is also supported by recent calculations (Hori and Ogihara 2020 ) showing the total mass loss of hydrogen-rich envelopes around TRAPPIST-1 planets is anyway likely higher than the amount of hydrogen-rich gas they can accrete during their formation.…”
Section: Constraints From Numerical Modellingsupporting
confidence: 81%
“…This stems from the fact that any significant change of H 2 content—e.g. arising from variations in the hydrogen-rich gas accretion rates during the planet formation phase (Hori and Ogihara 2020 ) or from variations in the H 2 escape rates (Bolmont et al. 2017b ; Bourrier et al.…”
Section: Constraints From Numerical Modellingmentioning
confidence: 99%
“…Although transmission spectroscopy cannot rule out H2-dominated atmospheres containing highaltitude aerosols (Moran et al 2018), such configuration is in fact unlikely. This stems from the fact that any small variation of hydrogen content between planets, as expected from (1) variations in the hydrogen-rich gas accretion rates during the planet formation phase (Hori & Ogihara 2020) and from (2) variations in H2 escape rates (Owen & Mohanty 2016;Bolmont et al 2017;Bourrier et al 2017), are expected to produce large variations in density between planets (Turbet et al 2020) that are not observed (Grimm et al 2018;Agol et al 2020).…”
Section: Transmission Spectra Of the Planetsmentioning
confidence: 99%
“…Lee et al 2014), the continual recycling of the accreting gas around the planet (e.g. Ormel et al 2015;Cimerman et al 2017;Kurokawa & Tanigawa 2018;Kuwahara et al 2019), the delay of gas accretion by polluted envelopes (Brouwers & Ormel 2020), and disk dissipation (Ikoma & Hori 2012;Hori & Ogihara 2020). We have recently proposed the possibility of suppressing envelope accretion via a limit due to the disk accretion rate (Ogihara & Hori 2018), and similar solutions have been discussed in other studies (e.g.…”
Section: Introductionmentioning
confidence: 69%